Effect of flow rate, angle and height of spray of tractor-mounted boom sprayer on weeds control at wheat fields. - AL-Qazzaz, Kamal Muhsin Ali; AL-Lami, Hassanain A. (Al-Qadisiyah Journal of Pure Science, 2017)
An experiment was conducted to study the effect of flow rate, angle and height of spray of tractor-mounted boom sprayer on weeds control at wheat fields. Three treatments including two flow rate of flat fan nozzle tip (1.58 81.80) l/min, three spray angel for each flow rate including (65°, 80°, 110°) and three spraying Heights including (35, 50, 65)cm were studied in this experiment. This experimental was applied at one of wheat field located in Khan-Beni Saad in Diala Government . Selective herbicide Shevalier were used in this study the following parameters were studied volume median Diameter (VMD), Converge, effective field capacity for sprayer, the damage percentage that resulted from drifting, the percentage of weed control after 6 weeks from spraying, the percentage of inhibition growth of weed and the total productivity of wheat, split-split plot design under randomized complete block design (R.C.B.B) with three replications. Main plots were specified for spray height while the subplot was the spray angle and the flow rates were the sub-sub plot. Results can be summarized as follows: 1. The increasing in flow rate of herbicide in nozzle tip (1.58-1.8 liter/min) give in produce increasing in volume median diameter and coverage that lead to increase efficient of weed control and inhibition weed growth (4.200-4.287) tin/hector. In addition to decrease harm effect that come from drifting with rate (3.33-4.00) harm degree. 2. The increasing in angle & height of spray (65, 80, 110), (35, 50, 65)cm. produce increase coverage and harm effect as a result of drafting, and also produce increase percentage of control and inhibition of weeds growth and increase crop yields with rate (4.058, 4.233, 4.440) tin/hector for spray angles, with rate (4.133, 4.225, 4.371) tin/hector for spray heights. 3. The interaction of flow rate and spray angle produce increase the coverage that increase percentage of inhibition weed growth, where the maximum rates of them (60.8)drop/cm2 , (97.53%) consequently. 4. The interaction between flow rate factor and height spray factor have no a signification effect on the studied characteristic. 5. The interaction of spray angle and height spray produce increase the coverage that increase percentage of weed control and inhibition of weed growth that increase crop yields that reach maximum level (4.525) tin/hector.